Pengaruh Social Media Marketing terhadap Purchasing Decision dengan Brand Image sebagai Variabel Mediasi - Latifah, Fitriana Nurul (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze the influence of social media marketing on purchasing decisions, with brand image as a mediating variable. The research employs a causal quantitative method using path analysis. The sample consists of 160 respondents selected through a nonprobability sampling technique. Data testing techniques include vailidity and reliability tests, while data analysis is conducted using descriptive statistics and multivariate analysis. The findings indicate thath social media marketing significantly influences purchasing decisions, both directly and through brand image as a mediating variabele. These results suggest that the more effective a company’s social media marketing strategy. The greater the likehood that consumers will make a purchase. Additionally, a positive brand image strengthens the relationship between social media marketing and purchasing decisions, ultimately enhancing customer loyalty. The conclusion of this study provides insight for fast-food restaurant industry players in Surabaya to further optimize their digital marketing strategies, not only by increasing their presence on social media, but also by building a strong brand image to encourage consumer purchases. Keywords: Brand Image, Purchasing Decision, Social Media Marketing.